The effect of local chemical ordering on Frank-Read source activation in a refractory multi-principal element alloy. (November 2020) - Smith, Lauren T.W.; Su, Yanqing; Xu, Shuozhi; Hunter, Abigail; Beyerlein, Irene J.
Abstract: In this work, we investigate the operation of Frank-Read (FR) sources in a refractory multi-principal element alloy (MPEA). Simulations of discrete dislocation motion in MPEAs is enabled by the development of a phase field dislocation dynamics model that treats the atomic-scale fluctuations in lattice energies across the glide plane, present due to local ordering in the chemical composition within the nominally random MPEA atomic structure. We consider, through simulation, a range of length scales over which ordering occurs, varying from short-range lengths, a few times dislocation core width, to long-range lengths, an order of magnitude longer than the core. Characteristic of this body-centered cubic MPEA, the simulations also include screw/edge character dependence in glide resistance, as informed by atomic scale simulation. The critical stresses to activate the source for the same source size are found to be statistically distributed, as a direct consequence of the underlying variation in lattice energy. Analysis of critical state for activating edge and screw FR sources in the MPEA reveals that FR source operation occurs via a two-step mechanism, involving athermal kink-pair formation, unlike the conventional FR source operation in a material with no composition fluctuations. This mechanism lowers the average critical stress required to activate the FR source and causes the statistical dispersion in critical stress to depend on the range of composition ordering. More importantly, it leads to a more severe dependence of source strength on FR source length than predicted by line tension alone. Graphical abstract: Image 1 Highlights: A phase-field dislocation dynamics model is developed for refractory MPEAs. Frank-Read sources in an MPEA are statistical in nature due to variations in local chemical clustering. Frank-Read sources in an MPEA operate with a distinct mechanism from those in conventional alloys. This mechanism leads to a much stronger source size dependence than predicted by line tension alone.